Plant succession in montane forest of Cameron Highlands - Sidek Omar, Nur Shifatil Ulya (2019)
The plant succession in montane forest of Cameron Highlands was studied in one-year old site on man-made (encroachment) degraded area (Site 1) and artificially cleared area (Site 2) of Cameron Highlands. The purpose of this study was to evaluate plant succession species in montane forest of Cameron Highland. On each site, two plots were established for both Site 1 and Site 2, and plant regeneration were observed for every three months period. The species composition and plant communities between two sites were then compared. Results showed that a total of 33 species from 22 families in Site 1 and 35 species from 23 families were recorded in Site 2. Family of Compositae contributed the highest number of species in both sites for every observation. At site 1, the dominant species was Ageratum conyzoides (IVi=26.51%) meanwhile in Site 2, the dominant species was Cuphea carthagenensis (IVi=35.95%) in one-year old sites. The vegetation communities at both sites were dominated mainly by weedy herbaceous, ferns and woody saplings. In one-year old sites, only Trema tomentosa and Homalanthus populneus managed to survive in weedy herbaceous dominated area. Shannon-Weiner Index showed that the diversity varies in both sites. The results showed that during early successional stages, both sites were highly dominated with weedy species which prevent the establishment of native successional species. In term of ecosystem restoration, the degraded area should be planted with native species and should not rely to natural succession.